Effect of the Artificial Sweetener, Acesulfame Potassium, a Sweet Taste Receptor Agonist, on Glucose Uptake in Small Intestinal Cell Lines - Zheng, Ye (2012)
Sweet taste receptors may enhance glucose absorption. AIM: To explore the cell biology of sweet taste receptors on glucose uptake. HYPOTHESIS: Artificial sweeteners increase glucose uptake via activating sweet taste receptors in the enterocyte to translocate GLUT2 to the apical membrane through the PLC βII pathway. METHODS: Caco-2, RIE-1, and IEC-6 cells, starved from glucose for 1 h were pre-incubated with 10 mM acesulfame potassium (AceK). Glucose uptake was measured by incubating cells for 1 to 10 min with 0.5–50 mM glucose with or without U-73122, chelerythrine, and cytochalasin B. RESULTS: In Caco-2 and RIE-1 cells, 10 mM AceK increased glucose uptake by 20~30% at glucose ≥ 25 mM, but not in lesser glucose concentrations (≤10 mM), nor at 1 min or 10 min incubations. U-73122 inhibited uptake at glucose ≥ 25 mM and for 5 min incubation; chelerythrine and cytochalasin B had similar effects. No effect occurred in IEC-6 cells. SUMMARY: Activation of sweet taste receptors had no effect on glucose uptake in low (<25 mM) glucose concentrations but increased uptake at greater concentrations (≥ 25 mM). CONCLUSIONS: Role of artificial sweeteners on glucose uptake appears to act in part by effects on the enterocyte itself.